The Key to Success in Speaking Indonesian in the Era of Globalization: A Study of Dell Hymes' Sociolinguistic Theory - Alghony, Ahmad Bustami; Akhmad Tabrani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to improve the Indonesian language in an era of increasingly advanced globalization. Research focused on communication errors or speech acts in everyday life when Indonesian is used in conversation. The method used uses qualitative research methods with content analysis techniques from language that is often used in everyday life. The results of the research show that in Indonesian, in general, there are still many errors in pronunciation. The use of Indonesian is often underestimated by some people in general. The use of language is considered a normal thing and it is not important to blame each other when speaking. The form of speech in the concept of everyday interaction is the object of study in this research. Through sociolinguistic theory, Hymes dissects an utterance in language through eight aspects which are usually called SPEAKING, namely: background and situation, communication participants, purpose, sequence of actions, and tone or attitude. Through these eight elements, this research is focused and can be well directed. So this form of research will later become a key in exploring success in Indonesian.